The Collector's Voice: Critical Readings in the Practice of Collecting Volume 4 Contemporary Voices - Pearce, Susan; Martin, Paul (Aldershot Ashgate, 1988)
The Collector's Voice is a major four-volume project which brings together in accessible form material relevant to the history and practice of collecting in the European tradition from c. 1500 BC to the present day. The series demonstrates how attitudes to objects, the collecting of objects, and the shape of the museum institution have developed over the past 3000 years. Material presented includes translations of a wide range of original documents: letters, official reports, verse, fiction, travellers' accounts, catalogues and labels.
General preface -- Introduction / Susan Pearce and Paul Martin -- Talk between men and women -- Consuming voices -- Talking collectibles -- Collecting stores -- Discourses of possibility -- Future voices -- Bibliography -- Index
Keywords: 20th Century (1901-2000); Collecting; Cuckoo